Lookup Table Based Intelligent Charging and Balancing Algorithm for Li-ion Battery Packs - Velho, Ricardo L. (2020)
Submitted by CALADO (rc@ubi.pt) on 2020-01-06T17:26:49Z No. of bitstreams: 1 6.4.102_IS_4_2018.pdf: 1052891 bytes, checksum: 28324b844050a418b51c78e164254604 (MD5)